A smart kid's guide to avoiding online predators - Jakubiak, David J. (New York : PowerKids Press, 2010)
Discusses the dangers of online predators and Internet safety for young readers, and provides tips and advice on ways to avoid becoming a victim of an online predator.
Danger on the web -- Who is out there? -- How problems start -- Keeping your cool -- Fighting back -- Getting help -- Going after a predator -- Keeping yourself safe -- Keep it online.
Includes index.
Library Media Connection starred
School Library Journal
Wilson's Children
Library Media Connection starred, January 2010
School Library Journal, December 2009
Keywords: Children and strangers -- Juvenile literature; Internet and children -- Juvenile literature; Internet -- Safety measures -- Juvenile literature; Safety education -- Juvenile literature; Internet; Internet -- Safety measures; Safety education; Strangers; Internet; Internet -- Safety measures; Safety education; Strangers